Nurses' Knowledge with Prevention of Nosocomial Infections in Postoperative Patients at Labuang Baji Hospital Makassar - Ahmad, Muhammad Iqbal; Wahyuni, Ria; Solehudin, Solehudin; Betan, Abu Bakar; Rante, Anshar; Rahmat, Rezqiqah Aulia (International Journal of Health Sciences, 2023)
Nosocomial infections can be defined as infections that are acquired or that occur in hospitals. Nosocomial infections can occur in patients, health workers, and also everyone who comes to the hospital. Infections that exist in this health care center can be transmitted or obtained through health workers, sick people, visitors who have career status or due to hospital conditions. In general, in nosocomial infections, patients who enter the hospital and cause symptoms of infection after 3 times 24 hours after the patient is hospitalized. The purpose of this study was to determine the relationship between nurse knowledge and prevention of nosocomial infections in postoperative patients at Labuang Baji Makassar Regional General Hospital. This type of research is descriptive analytic with a cross sectional approach. The sample in this study were 26 nurses who served in the surgical room at the Makassar Labuang Baji Regional General Hospital. Data analysis through a computerized program  = 0.05. The research variables consisted of independent variables; knowledge, education, length of work. The results showed that: the level of knowledge P value = 0.000, the level of education p value = 0.000, and the length of work p value = 0.107. The conclusions in this study are: There is a relationship between the level of knowledge and education with the prevention of nosocomial infections in postoperative patients and there is no relationship between length of work with the prevention of nosocomial infections in postoperative patients.